Avoiding disease mongering: A checklist for vascular physicians and researchers. Issue 181 (September 2019) - Frappé, Paul; Haller, Dagmar M.; Roméas, Andrea; Bertoletti, Laurent; François, Mathilde; Robert-Ebadi, Helia; Righini, Marc
Abstract: Disease mongering is an expression created in 1992 by a medical journalist, Lynn Payer, to qualify the "selling of sickness that widens the boundaries of treatable illness in order to expand markets for those who sell and deliver treatments". This interesting concept led us to question whether, as researchers with publication and career interests in superficial vein thrombosis, we were not shaping a benign condition into a disease. Since the publication of the CALISTO trial in 2010, anticoagulant management of superficial vein thrombosis remains debated. Issues raised, such as the cost-effectiveness of the treatment strategy, the use of a composite endpoint including death, the low event rate without mortality reduction and conflict of interest due to industrial funding. We searched Embase, Medline, Web of science, and Opengrey databases to review all aspects about disease mongering raised in the literature and created a checklist with seventeen items. We used this checklist as support for a narrative review, questioning known literature on superficial vein thrombosis. The main issues pointing towards disease mongering concerned definition and promotion; whereas management seemed rather spared. Many arguments could be counterbalanced, but researchers should pay particular attention to three major points: exaggeration of the severity of the disease and potential adverse outcomes without treatment, promotion by opinion leaders, and an openly declared, yet undoubtedly present, conflict of interest situation. Highlights: Disease mongering describes the "selling of sickness in order to expand markets for those who sell and deliver treatments". As researchers with publication and career interests, we could be prone to disease mongering. A checklist of arguments of disease mongering has been used to question literature on superficial vein thrombosis (SVT). Researchers on SVT should pay attention to exaggeration of severity, opinion leaders and conflict of interest situation.